(untitled) (Jurnal Teknologi (Sciences & Engineering), 2012)
This paper presents a new and simple design of gas cell for the use of intra–cavity fibre laser sensors. This design utilizes gradient–index fibres for collimation to realize a miniature gas cell of very small diameter. By using the Gaussian field approximation and ray transformation, the gas cell is analyzed and optimized. It is found that gradient–index fibre based cells could achieve lower coupling loss of nearly 10 dB at a separation of 20 mm and allow for additional tolerance to certain misalignments, in comparison with those single–mode fibre based cells. A new–design cell is fabricated and its coupling loss is tested with a 1550 nm laser. Good agreement in the analysis and experimental results is obtained, indicating that the design could be feasible in practical gas sensing. Key words: Gradient–index fibre based cell; gradient–index fibre collimator (GIFC); coupling loss; misalignments; intra–cavity fibre gas sensor